Effectiveness of Module Based Learning regarding Facility Based Newborn Care in terms of knowledge and practices among nursing students - Kumari, Minal; Kumar, Yogesh; Kaur, Parvinder (International Journal of Contemporary Pediatrics, 2019)
ABSTRACT Background: Mobile Applications are being developed at a rapid speed and are intensively used by students. It can help to achieve better performance in organizing, managing, and monitoring classroom activities. Aims and objectives: Present study aimedto assess and compare the knowledge and practice regarding FBNC among nursing students in MBL group and MABL group before and after the administration of MBL and MABL. The conceptual framework of the study was based on CIPP model by Stufflebeam. Methods: A Quantitative research approach with quasi-experimental and non-equivalent controlgroup pre–test post–test design. The study was conducted at two nursing colleges of Ambala, Haryana. A total of 70 B.Sc. Nursing 3rd Year students, randomly allocated to 2 groups i.e. 35 in MBL and 35 in MABL. The tool used for the study consisted of structured knowledge questionnaire and observational check list was used to assess knowledge and practices by OSCE method of nursing students regarding FBNC. Data collection was done in January, 2017. The obtained data was analyzed and interpreted in terms of objectives and research Results: Findingsof the study indicate that revealed that mean post- test knowledge and practices score in MBL group (21.4 ±0.89) and in MABL group (22.4 ± 0.54) was significantly higher than pre-test knowledge score in MBL group (14.6±15.0) and in MABL group (16.2±17.0). Also, the mean post-test practice score in MBL group (38.1±1.91) and in MABL group (38.9± 1.20) was significantly higher than pre-test practicescore in MBL (20.4 ± 3.70) as well as in MABL group (20.5 ± 4.26). Mild positive significant relationship (r=0.03) was found between post test score of knowledge and practices Conclusion: MABL was more effective in developing the practices of nursing students regarding FBNC than MBL.